Peptide-size-dependent active transport in the proteasome - Zaikin, A.; Pöschel, Thorsten (EPL - Europhysics Letters, 2005)
We investigate the transport of proteins inside the proteasome and propose an active-transport mechanism based on a spatially asymmetric interaction potential of peptide chains. The transport is driven by fluctuations which are always present in such systems. We compute the peptide-size-dependent transport rate which is essential for the functioning of the proteasome. In agreement with recent experiments, varying temperature changes the transport mechanism qualitatively. © EDP Sciences.